2016
DOI: 10.1249/mss.0000000000000894
|View full text |Cite
|
Sign up to set email alerts
|

Organized Sport Trajectories from Childhood to Adolescence and Health Associations

Abstract: This study identified unique, sex-specific trajectories of organized sport participation. The differences in health outcomes between trajectory classes, such as participants with consistent sport participation having more preferable health outcomes at the age of 20 yr, support the internal validity of the trajectories. Strategies are needed to identify and encourage those in the dropout trajectory to maintain their participation and those in the nonparticipator or joiner trajectories to join sport earlier. Spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
104
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(118 citation statements)
references
References 35 publications
14
104
0
Order By: Relevance
“…It is rational to believe that this support influences behaviors related to sports participation in adulthood. Our findings are also similar to Howie, McVeigh, Smith, Straker 26 , who reveal that teasing among girls, body image, feeling that sports are not feminine coupled with the stereotypes of sex roles in society, increases the participation of boys and the reduces the participation girls in sports or physical activity from an early age 26 . In our study, lower levels of education were associated with non-sports participation throughout life.…”
Section: Discussionsupporting
confidence: 90%
“…It is rational to believe that this support influences behaviors related to sports participation in adulthood. Our findings are also similar to Howie, McVeigh, Smith, Straker 26 , who reveal that teasing among girls, body image, feeling that sports are not feminine coupled with the stereotypes of sex roles in society, increases the participation of boys and the reduces the participation girls in sports or physical activity from an early age 26 . In our study, lower levels of education were associated with non-sports participation throughout life.…”
Section: Discussionsupporting
confidence: 90%
“…In Japanese children [27], the rate of participation in organized sports similarly decreased from 100% in 2002 to 79.4% in 2014, causing a decrease in the average number of members in sports clubs (26.7 members per club in 2002 and 21.8 in 2014). Howie et al [28] reported that one-third of girls and boys after the age of 8 years in Western Australia dropped out of playing sports. For example, lower household income, main language spoken at home (non-English), lower parental education and child not taken to a sporting event were predictors of dropout from organized sports [29].…”
Section: Discussionmentioning
confidence: 99%
“…As the level of competition in organized sports leagues increase, those who do not desire to compete at a higher level may simply drop out of sports. 31 A study indicated that girls who do not become involved at a young age (,8 years) will likely not become involved as they get older, but boys may join sports in adolescence, even if they are not involved earlier. 31 Because some health benefits are seen with any organized sports participation, community offerings for girls and boys at multiple levels of competition could support greater participation.…”
Section: Role Of Community Organizationsmentioning
confidence: 99%
“…31 A study indicated that girls who do not become involved at a young age (,8 years) will likely not become involved as they get older, but boys may join sports in adolescence, even if they are not involved earlier. 31 Because some health benefits are seen with any organized sports participation, community offerings for girls and boys at multiple levels of competition could support greater participation. The business model of most community youth sports organizations has drifted toward supporting higher and higher playing levels (eg, "elite" levels).…”
Section: Role Of Community Organizationsmentioning
confidence: 99%